Kant and the Problem of Evil - Pieniążek, Paweł (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Kant consequently achieved the moral subjectivation of evil, referring it solely to human will and to the moral law established by it. The article shows, however, the difficulties with explaining the possibility of evil in the mature thought of Kant. They emerged from the difficulty with determining the relation between will and moral law and underlay the evolution of his understanding of evil. If in the Groundwork of the Metaphysics of Morals and in the Critique of Practical Reason Kant identifies will with moral law, abolishing in this way the possibility of the choice of good and evil, in Religion within the Bounds of Bare Reason he tries to establish this possibility. The tension between the moral and historical dimensions of evil is also shown.